التخطيط الاستراتيجي للموارد البشرية واثره في تحسين اداء الافراد في المؤسسة الاقتصادية - رحاب, قاسمي; يسرى, قاسمي; اسماء, دبيلو (University of eloued جامعة الوادي, 2020)
"الملخص تأتي هذه الدراسة لمناقشة الإشكالية ""حول اثر التخطيط الاستراتيجي للموارد البشرية في تحسين أداء الأفراد في مؤسسة توزيع الكهرباء والغاز بالوادي "" ، و تهدف إلى قياس اثر التخطيط الاستراتيجي للموارد البشرية على أداء أفراد بمؤسسة توزيع الكهرباء والغاز بالوادي ،مستخدما في ذلك تحليل البيانات ببرنامج spss.v25 وتم توزيع استبانه اشتملت العينة على 52 استمارة ، وذالك اعتمادا على المنهج التحليلي الوصفي ، حيث توصلت الدراسة إلى وجود اثر ايجابي دو دلالة إحصائية معنوية بين التخطيط الاستراتيجي للموارد البشرية و تحسين أداء الأفراد بمؤسسة توزيع الكهرباء والغاز بالوادي , وذلك من خلال عدة أبعاد ""رسالة المؤسسة , تحديد أهداف المؤسسة , تحليل البيئة , تحديد الطلب "". ""Recapitulaution: urces in improving the performance of individuals in the Electricity and Gas Distribution corporation in El oued . It olso aims to measure the impact of strategic planning for human resources on the performance of individuals in the valley Electricity and Gas Distribution corporation . This study comes to discuss the Problem ""about the impact of strategic planning for human reso A formalities was distributed that included the sample on 52 formalities. Based on the descriptive analytical approach , we have relied on the spss .v25 system , where the study found a positive impact and a significant statistical indication between strategic planning for human resources and impeoving the performance of individuals in the Electricity and Gas Distribution corporation in the vally , through several dimensions Institutional mission , defining the institution s objectives , analyzing the environment , determining the demand. "
مذكرة ماستر ادارة اعمال
Keywords: تخطيط استراتيجي للموارد البشرية , تقييم الأداء , مؤسسة توزيع الكهرباء والغاز .; The strategic planning for human resources , performance assessment , Electric and gas company .